Community empowerment in an effort towards quality health - Suprapto Suprapto; Darmi Arda; Maria Kurni Menga; Lamria Situmeang (Edukasi Ilmiah Indonesia, 2024)
Community empowerment in the context of health has become a significant focus of efforts to improve overall public health. Increasing public knowledge and health awareness is this empowerment's primary goal. Through various methods such as health education, active community participation, use of information technology, resource support, and continuous evaluation, empowerment efforts aim to create an environment where people are more aware of the importance of health and have sufficient knowledge to make informed decisions regarding their health. The results of this empowerment include improved healthy living behaviours, reduced health disparities, increased access to equitable health services, and the development of more independent and empowered communities. By strengthening community empowerment, it can be expected that overall public health will improve, and creating a society that is more health-conscious and able to contribute to maintaining health together can create an environment where people are more health-conscious, have enough knowledge to make good decisions regarding their health, and actively contribute to maintaining health together